247. From CTDI-in-air to equilibrium dose. (December 2018) - Spampinato, S.; Gueli, A.; Raffaele, L.
Abstract : Purpose: CTDI metric is currently used for standardized measures of dose-output. Recently, however, strengths/weaknesses of CTDI have been debated: (1) 100 mm-long ionization chambers may not be sufficiently long to measure the tails of scattered dose distribution, (2) phantoms used are shorter than an adult torso. Two approaches have been proposed: use longer ionization chambers and phantoms, or using small probes to determine the equilibrium dose ( D eq ) [1] . The present study proposes a method based on CTDI-in-air metric to calculate D eq following the approach suggested by Li et al.[2] . The method was also validated using radiochromic films. Methods: First, P H and P B parameters were evaluated for the conversion of weighted-CTDI (CTDIw) to CTDI-in-air. Measurements were performed with a 100 mm-pencil chamber in standard setup with Head and Body phantoms and in air. Subsequently, D eq was calculated using the values reported by the CT-console and those obtained with CTDI-in-air and P / P H with values suggested by Li et al.. Finally, a method to calculate CTDI-in-air with radiochromic films has been validated. Strips of film were irradiated with the same setup and calibrated using a standard procedure. Dose profiles were extracted and CTDI-in-air calculated and validated with standard measurements. Results: Table 1 shows D eq values obtained for CTDIw and CTDI-in-air. Differences are higher for smaller collimations, not routinely used in clinical practice. For radiochromic film the maximum difference compared to standard measurements is 10%, but the average error is about 7% for a voltage of 120 kV and 2% for 140 kV. Conclusions: CTDI-in-air can be measured quickly and could be helpful in calculating Deq. Radiochromic films allow measuring CTDI-in-air for standard and wider collimations (i.e. ConeBeam-CT).